ANALISIS PENERAPAN ETIKA PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SEMARANG - Himawan Shaputra Munandar, Ravi; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
Public service is one of the most important things in the process of organizing a country. Public services are closely related to the system and procedures for service delivery rules. The existence of ethics in the implementation of public services is the value of employee behavior. The application of service ethics is not yet fully optimized. This is because there are still many public service providers who do not comply with public service ethics when providing services. The purpose of this study is to analyze the application of public service ethics by the Semarang City Dispendukcapil and analyze what are the supporting factors and inhibiting factors of the application of public service ethics. The type of research used is descriptive qualitative with data collection methods in the form of interviews, observation, documentation, and literature study. The results showed that the order dimension has been implemented optimally, while the efficiency, productivity, and moral awareness dimensions are still not optimal in its implementation. The supporting factors are organizational factors and service facilities factors, while the inhibiting factors are personnel factors, namely communication conveyed to the public is still confusing, speed in providing services, care that needs to be improved. Thus, it can be concluded that the implementation of public service ethics at Dispendukcapil has not fully run optimally. The existence of problems that are not optimal requires improvement and improvement so that the application of service ethics is more optimal and can have a good impact on public services.